RESPONSABILIDADE SOCIAL NAS MICROEMPRESAS: ESTUDO DE CASO DE MICROEMPRESAS DA BAIXADA LITORÂNEA E REGIÃO DOS LAGOS DO ESTADO DO RIO DE JANEIRO - Khalil, Raja Oliveira (2007)
This dissertation treats of the subject Social Responsibility, fear that has been discussed in the most varied debate vehicles and critic and, I motivate of countless studies, mainly, in companies of great load. The objective of this study is to identify in researched companies it´s relationship with the practice of Social Responsibility, for so much, it was done necessary a bibliographical research and in websites that contributed to the construction of a theoretical referencial capable to elucidate and to beacon the results of the field research. The used methodology looked for, through a structured questionnaire, collect given of hundred and twenty-six managers of small businesses in ten municipal districts of the area denominated "Baixada Litorânea" in the State of Rio de Janeiro. This way, it was possible to quantify and to analyze the behavior of the researched companies as the practice of Social Responsibility. When analyzing the obtained results, it is noticed the managers fragility in relation to the theme, little are the actions and, even so, they are not understood as Social Responsibility, but, as a "common sense" subject